Segitiga Friksi dalam Organisasi: Model Integratif Ketidakjelasan Peran, Ketergantungan Tugas, dan Perbedaan Tujuan - Ravel Anwar (Jurnal Administrasi Bisnis, 2025)
Modern organizational dynamics posit conflict as a logical consequence of complex structural interactions rather than a mere behavioral anomaly. This study aims to synthesize recent literature to develop a predictive conceptual model that integrates role ambiguity, task interdependence, and goal differences as simultaneous determinants. This study conducted a Systematic Literature Review (SLR) following the PRISMA 2020 protocol. Data were extracted from Scopus, ScienceDirect, and Google Scholar databases spanning 2020–2025 to capture current dynamics. Through rigorous selection, 45 empirical articles were analyzed using thematic analysis assisted by NVivo 12. The study confirms the formation of a "triangle of friction" mechanism. Role ambiguity is identified as the breeding ground for operational confusion. This impact is subsequently amplified by task interdependence as a contagion mechanism and significantly exacerbated by goal differences that polarize inter-unit relationships. This study concludes that destructive conflict results from systematic interaction, not random occurrence. Managerial implications emphasize a holistic approach through periodic work design audits, revising job descriptions to minimize ambiguity, and cross-functional goal alignment to effectively mitigate organizational structural vulnerabilities.